Fat products - Alexei Alexandrov (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
The economics literature generally considers products as points in some characteristics space. Starting with Hotelling, this served as a convenient assumption, yet with more products being .exible or self-customizable to some degree it makes sense to think that products have positive measure. I develop a model where .rms can oþer interval long .fat. products in the spatial model of diþerentiation. Contrary to the standard results pro.ts of the .rms can decrease with increased diþerentiation - there is a standard eþect of lowering the incentive to cut prices, but there is also an incentive to provide more content sometimes resulting in lower pro.ts. Consumer welfare increases unambiguously with respect to the standard model of Salop. I also .nd that it is pro.table for .rms to commit as an industry not to make fat products. If one .rm is a leader and another is a follower, the leader accommodates the follower by settling for less pro.ts if diþerentiation is small.
Keywords: 330; Produktdifferenzierung; Hotelling Modell; Reisekostenansatz; Monopol; Duopol; Theorie